On the largest analytic set for cyclic operators - A. Bourhim (International Journal of Mathematics and Mathematical Sciences)
We describe the set of analytic bounded point evaluations for an arbitrary cyclic bounded linear operator T on a Hilbert space ℋ; some related consequences are discussed. Furthermore, we show that two densely similar cyclic Banach-space operators possessing Bishop's property (β) have equal approximate point spectra.